PENGARUH PENDIDIKAN KESEHATAN SADARI DENGAN MEDIA SLIDE DAN BENDA TIRUAN TERHADAP PERUBAHAN PENGETAHUAN WUS - Utut Andita (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
In 2012 there were 1.7 million women suff ering from breast cancer, the disease is the most common cause of death in women (IARC, 2013). Deaths from breast cancer due to a delayed in diagnosis. Breast Self Examination (BSE) is one of the method for early detection of breast cancer, by doing this way routinely proven to lower the mortality rate of breast cancer about 25–30%. However,actually there are many Women of Childbearing Age (WCA) who don’t know about BSE. The aim of this study was to analyses the infl uence of SADARI health education on WCA knowledge. The study design was used One Group Pre Test Post Test with Pre Experimental Design. Population of this study wasWCA at PKK of RW 03 in Karang Widoro Village, Malang, numbering 113 people and samples used by 31 people with incidental sampling technique. Instrument was used by using questionnaires. The results of analysis using the Paired t-test is ρ = 0.00  α = 0.05. This means that there are infl uence BSE healtheducation with slide and artifi cial object media to change WCA knowledge. The conclusion of this study is increase very signifi cantly in the respondents’ knowledge after health education BSE with merge slide and artifi cial object media. Suggestions for provider to conduct health education by using appropriate media merger.Keywords: BSE, Knowledge, WCA